Archaeological Remote Sensing in the 21st Century: (Re)Defining Practice and Theory - Verhoeven, Geert; Cowley, Dave; Traviglia, Arianna (MDPI - Multidisciplinary Digital Publishing Institute, 2021)
Remotely sensed data from either air- or spaceborne platforms are often leveraged for archaeological or more general cultural heritage goals. However, despite the steady developments in remote sensing technology over the past three decades, the thoughtful integration of data sources and methods into theoretically aware archaeological practice remains relatively underdeveloped. This volume contains nine contributions which, each in their way, address different theoretical dislocations and practical shortcomings in the use of remote sensing products within archaeological practice. These contributions provide the reader with food for thought on these challenges, and so contribute to archaeological remote sensing as a more mature interdisciplinary field characterised by explicit, thoughtful, and theoretically engaged approaches to understanding the past.